A new approach to multiplication for gifted children - Kravčenkienė, Violeta; Narkevičienė, Bronė (Lietuvos matematikos rinkinys, 2018)
The article presents the case of mathematical education of gifted children in Kaunas city interdisciplinary program in the third grade. The theoretical basis for such education is the application of differentiated teaching using external differentiation – the program is aimed at the gifted children in the whole city. Additional aspects of differentiated teaching: grouping of learners according to the skill level, selection of non-standard curriculum content, teamwork and individualized assessment.